FROM THE EDITOR - Lategan, Bernard C. (Scriptura, 1981)
We are honoured to begin Scriptura 4 with a contribution by Professor Hendrikus Boers of Emory University in Atlanta, Georgia, where he teaches New Testament at Candler School of Theology. Recently he spent some time in Stellenbosch as visiting scholar and was responsible for several seminars and lectures, inter alia a paper read before the NT Society of S A. The present article is based on material from a forthcoming book, entitle "Who was Jesus?" and we are glad to offer our readers this form of ‘pre-view’.